2021
DOI: 10.1096/fj.202002016r
|View full text |Cite|
|
Sign up to set email alerts
|

mTORC1 promotes mineralization via p53 pathway

Abstract: The objectives of our study were to investigate the roles of mTORC1 in odontoblast proliferation and mineralization and to determine the mechanism by which mTORC1 regulates odontoblast mineralization. In vitro, MDPC23 cells were treated with rapamycin (10 nmol/L) and transfected with a lentivirus for short hairpin (shRNA)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 43 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…mTORC1 is essential for the osteo/odontoblastic differentiation of dental stem cells [ 11 13 ]. In our recent study, we confirmed that mTORC1 promoted mineralized matrix secretion by odontoblasts via the p53 signaling pathway [ 14 ]. Additionally, we found that the expression levels of cluster of differentiation 63 (CD63) and apoptosis-linked gene 2-interacting protein (Alix) changed with changes in mTORC1 activity and that predentin was thicker in molars in 6-month-old mice with activated mTORC1.…”
Section: Introductionmentioning
confidence: 57%
“…mTORC1 is essential for the osteo/odontoblastic differentiation of dental stem cells [ 11 13 ]. In our recent study, we confirmed that mTORC1 promoted mineralized matrix secretion by odontoblasts via the p53 signaling pathway [ 14 ]. Additionally, we found that the expression levels of cluster of differentiation 63 (CD63) and apoptosis-linked gene 2-interacting protein (Alix) changed with changes in mTORC1 activity and that predentin was thicker in molars in 6-month-old mice with activated mTORC1.…”
Section: Introductionmentioning
confidence: 57%
“…Recent studies on mTORC1 in tooth germs have been limited to tooth development. 46 For instance, studies have shown that inhibition of mTORC1 causes proliferation defects and excessive cell death, resulting in facial growth defects and wrinkles. 27 What's more, mTORC1 inhibition disrupts enamel cell adhesion, proliferation, and differentiation, leading to defective tooth formation and malformations.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by our team indicated that mTOR pathway activation significantly enhanced dentin formation. 27 In this study, we conducted further RNA sequencing to investigate the potential involvement of miR-3074-3p in the odontogenic differentiation of hDPSCs. MiR-3074, first reported in 2015, 35 was mainly involved in tumor development, cell metabolism, and tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 Our previous study has demonstrated the involvement of the mTOR signaling pathway in regulating the mineralization process of odontoblast cells. 27 This finding suggested that there might be molecular pathways involved in the regulation of odontogenesis under the activation of the mTOR pathway.…”
Section: Introductionmentioning
confidence: 97%